Family Resilience with Parents Who Were Victims of Layoffs during the Covid-19 Pandemic - Savina, Kus Fiani; Suryanto, Suryanto (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
The COVID-19 pandemic has clearly had a negative effect on society, one of which is the number of workers who have been laid off and most of them are parents who have to maintain their families economically, starting from the cost of their children's education, household needs, and daily needs. Therefore, resilience is needed for every family in facing this pandemic. This study aims to describe and analyze family resilience in the presence of parents who are victims of layoffs during the COVID-19 pandemic. This research uses a qualitative approach with data collection in the form of observation and in-depth interviews. The subjects in this study were three parents in a family who work as factory laborers who experienced layoffs during the COVID-19 pandemic. Parents who have children aged 6-15 years, and live together with their respective spouses. All participants live in Sidoarjo, Indonesia. The results showed that every family in which there are parents who are victims of layoffs has defense strategies in dealing with the pandemic, such as finding other jobs that can be done during the pandemic, managing household finances, doing activities that have a positive impact on the family, and increasing gratitude. This research is expected to provide practical solutions to the problems of families whose parents are victims of layoffs and can survive the pandemic.Masa pandemi COVID-19 jelas mengakibatkan efek negatif di kalangan masyarakat, salah satunya adalah banyaknya pekerja yang menjadi korban PHK dan sebagian besar merupakan orang tua yang harus mempertahankan keluarganya secara ekonomi, dari mulai biaya pendidikan anaknya, kebutuhan rumah tangganya, dan kebutuhan sehari-harinya. Maka dari itu, resiliensi sangatlah diperlukan bagi setiap keluarga dalam menghadapi masa pandemi ini. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis resiliensi keluarga dengan adanya orang tua yang menjadi korban PHK di masa pandemi COVID-19. Penelitian ini menggunakan pendekatan kualitatif dengan pengumpulan data berupa observasi dan wawancara mendalam (in-depth interview).  Subjek dalam penelitian ini merupakan tiga dari orang tua dalam keluarga yang berprofesi sebagai pekerja buruh pabrik yang mengalami PHK pada masa pandemi COVID-19. Orang tua yang memiliki anak usia 6-15 tahun, dan tinggal bersama dengan pasangannya masing-masing. Seluruh partisipan berdomisili di Sidoarjo, Indonesia. Hasil penelitian menunjukkan bahwa setiap keluarga yang didalamnya terdapat orang tua yang menjadi korban PHK memiliki strategi pertahanan dalam menghadapi masa pandemi, seperti mencari pekerjaan lain yang bisa dilakukan di masa pandemi, mengelola keuangan rumah tangga, melakukan kegiatan yang berdampak positif bagi keluarganya, dan meningkatkan rasa syukur.   Penelitian ini diharapkan dapat memberikan solusi praktis terhadap permasalahan keluarga yang orang tuanya menjadi korban PHK dan mampu bertahan di masa pandemi.